The Influence Of Service Quality, Product Quality, Location, And Store Atmosphere On Customer Satisfaction At Coffee Shop Opus Ex Animo Sidoarjo - Ismail, Andi Muhammad; Darmawan, Danni; Iskandar, Ridwan; Andini, Paramia (CV. SPDFHarmony, 2025)
Aim: This study aims to investigate the impact of four key marketing variables—service quality, product quality, location, and store atmosphere—on customer satisfaction at Coffee Shop Opus Ex Animo in Sidoarjo. The research is grounded in the growing competition among coffee shops in East Java and the urgent need to identify the most influential drivers of customer loyalty in the sector. Methods: A quantitative survey method was employed, targeting customers who had made dine-in purchases. Fifty respondents were selected through incidental sampling. Data were collected via structured questionnaires and analyzed using multiple linear regression with SPSS 22.0. Prior to regression, classical assumption tests such as validity, reliability, normality, multicollinearity, and heteroscedasticity were conducted to ensure robustness. Findings: The results revealed that all four independent variables significantly influenced customer satisfaction, both partially and simultaneously. Among them, location had the most dominant effect (β = 0.480, p < 0.001), followed by product quality, store atmosphere, and service quality. The adjusted R² value of 0.798 indicates that 79.8% of the variance in customer satisfaction could be explained by the model. Significance: The findings highlight the importance of strategic location as a competitive advantage in the café business. Furthermore, they underscore the necessity of managing service and product quality alongside the physical ambiance to sustain customer satisfaction. These insights provide actionable implications for retail entrepreneurs and marketers aiming to optimize customer experiences and business performance in a highly saturated marketplace.